Collaborative Strategies for Teaching Reading Comprehension: A Literature Review of Moreillon’s Framework and Its Relevance to Indonesian Universities - Rakhmasari, Dwi Lia; Pratiwi, Berlin Insan (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This article provides an extended conceptual and pedagogical review of collaborative strategies for teaching reading comprehension based on Judi Moreillon’s Collaborative Strategies for Teaching Reading Comprehension: Maximizing Your Impact (Moreillon, 2007). This study employs a qualitative literature review design to synthesize theoretical and empirical insights related to collaborative reading instruction. The study is framed within the pressing need to strengthen Indonesian students’ reading literacy, as national and international assessments consistently place Indonesia among the lowest performers in reading. These conditions reinforce the urgency for educators to adopt instructional practices that not only support comprehension but also cultivate meaningful engagement with written texts.Collaborative reading instruction is presented as a strategic approach in which lecturers, university librarians, and other educational partners jointly design, execute, and evaluate literacy-learning activities. Collaboration is defined as an equitable, voluntary, and interactive partnership where participants share responsibility for instructional decisions and student learning outcomes. Five collaborative teaching models support teaching, learning centers, parallel teaching, alternative teaching, and team teaching are elaborated as practical frameworks for enhancing reading instruction.The article further discusses seven core strategies for reading comprehension proposed by Moreillon: activating background knowledge, using sensory imagery, generating questions, making predictions and inferences, identifying main ideas, applying fix-up or self-monitoring strategies, and synthesizing information. These strategies guide learners through pre-reading, while-reading, and post-reading processes, enabling them to make connections to prior experiences, interpret textual cues, monitor comprehension, and construct integrated understandings of texts. Incorporating visual stimuli, intertextual connections, and student-centered questioning further enriches meaning-making. The discussion emphasizes the crucial shared roles of lecturers and librarians in resource selection, instructional planning, information-literacy support, and ethical use of sources, including guiding students in preventing plagiarism. A collaborative classroom–library structure promotes interdisciplinary learning, broadens access to quality reading materials, and fosters students’ critical engagement with diverse information sources.Overall, collaborative reading instruction is argued to be a relevant, context-appropriate, and practical solution for improving reading comprehension in Indonesian universities. Lecturers may adopt selected strategies based on classroom needs, resource availability, and instructional goals. When implemented consistently and thoughtfully, collaborative strategies promote active learning, increase student participation, and contribute significantly to more meaningful literacy experiences.